Best practices for the management of febrile seizures in children - Alessandro Ferretti; Antonella Riva; Alice Fabrizio; Oliviero Bruni; Giuseppe Capovilla; Thomas Foiadelli; Alessandro Orsini; Umberto Raucci; Antonino Romeo; Pasquale Striano; Pasquale Parisi (BMC, 2024)
Abstract Febrile seizures (FS) are commonly perceived by healthcare professionals as a self-limited condition with a generally 'benign' nature. Nonetheless, they frequently lead to pediatric consultations, and their management can vary depending on the clinical context. For parents and caregivers, witnessing a seizure can be a distressing experience, significantly impacting their quality of life. In this review, we offer an in-depth exploration of FS management, therapeutic interventions, and prognostic factors, with the aim of providing support for physicians and enhancing communication with families. We conducted a comprehensive literature search using the PubMed and Web of Science databases, spanning the past 50 years. The search terms utilized included "febrile seizure," "complex febrile seizure," "simple febrile seizure," in conjunction with "children" or "infant." Only studies published in English or those presenting evidence-based data were included in our assessment. Additionally, we conducted a cross-reference search to identify any additional relevant data sources. Our thorough literature search resulted in a compilation of references, with carefully selected papers thoughtfully integrated into this review.